ANALISIS KEPENDUDUKAN TERHADAP PERTUMBUHAN EKONOMI - Eka Adiputra (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2014)
Bojonegoro’s economic growth within 3 years (2010, 2011, and 2102) is the highest as the province of East Java categorized as Fast Growing Regions (TypologyKlassen). This means that the economic growth rate Bojonegoro greater than the achievement of economic growth in East Java province. However, the achievement of the highest economic growth progressively decreased. In this study, researchers tried to analyze the influence of demographic factors on the rate of economic growth. Factors studied population is the total population and the population dependency ratio of the load. Researchers will analyze the influence of the number of population and ratio of load dependence of the rate of population growth is declining. The method used in this research is descriptive analysis.